Reconstruction of Corporate Governance and Sustainability Reporting: Industry Association as Mediation - Wiyarni Wiyarni; Aminul Amin; Kadarusman Kadarusman (Journal of International Conference Proceedings, 2025)
This study aims to explore the role of industry associations in reconstructing corporate governance towards sustainability reporting. This study used industry association as intervening variable. The focus of the research is on public companies in Indonesia. The population of this study is 941 companies going public in Indonesia up to 2024, consisting of the manufacturing sector, basic material sector, and service sector. The sample in this study was 112 basic material companies, with observations for 3 years, so the total observations were 336. The collected data were analyzed using a statistical model that has been prepared to test the research hypothesis. This statistical analysis was conducted to evaluate the influence of corporate governance principles on sustainability reporting, taking into account the role of industry associations as mediating parties. The statistical analysis used SmartPls software. The results of this study show that corporate governance significantly influence the sustainability reporting. Industry association in this study is able to mediate the impact of corporate governance on sustainability reporting.